1997
DOI: 10.1007/bf02436059
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of various trace elements during germination of wheat, buckwheat and quinoa

Abstract: The practice of sprouting is widely used to improve the nutritional value of grain seeds. Several nutritive factors such as vitamin concentrations and bioavailability of trace elements and minerals increase during germination. The objective of this work was to study the enrichment of various essential trace elements during germination of wheat (Triticum aestivum), buckwheat (Fagopyrum esculentum), and quinoa (Chenopodium quinoa) seeds in order to improve their nutritional role as a source of bioavailable trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 14 publications
(14 reference statements)
2
58
1
2
Order By: Relevance
“…This allows to conclude that selenium accumulation in malt is proportional to its concentration in solution and it is practically linear. These results are similar to those found previously (Lintschinger et al, 1997) The most important parameter in the evaluation of the malting usability of rye grain is concentration of malt extract, estimated as the proporion of extractive substances obtained from malt produced from a given grain under optimal technological conditions. Concentration of malt extract varies in wide range, primarily depending on grain quality (Bùaýewicz et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This allows to conclude that selenium accumulation in malt is proportional to its concentration in solution and it is practically linear. These results are similar to those found previously (Lintschinger et al, 1997) The most important parameter in the evaluation of the malting usability of rye grain is concentration of malt extract, estimated as the proporion of extractive substances obtained from malt produced from a given grain under optimal technological conditions. Concentration of malt extract varies in wide range, primarily depending on grain quality (Bùaýewicz et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…It is known that germination may influence the level and bioavailability of the bioactive compounds (Lintschinger et al, 1997;2000;Katina et al, 2007;Tian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins break down into amino acids and water-soluble vitamins such as Bcomplex and vitamin C. At the same time there are reports that germination is effective in reducing phytic acid, flatulence causing oligosaccharides and polyphenols thereby increasing protein digestibility and improving sensory properties (Lintschinger et al 1997;Zanabria et al 2006;Khattak et al 2007). Recently, it has been reported that germination under different type of illumination has significant effect on biosynthesis of ascorbic acid and sprout yield of soybean and chickpea (Mao et al 2005;Khattak et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that germination may influence the level and bioavailability of the bioactive compounds (Lintschinger et al, 1997;Katina et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%